KAJIAN LITERATUR MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR - Athifah Damawah; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe and analyze the results of previous research on the use of the Discovery Learning model in improving the writing skills of elementary school students. This study employed a literature review method by collecting various relevant sources, such as scientific journals, research articles, books, and seminar proceedings. The sources used were drawn from journals indexed in Google Scholar and SINTA published between 2019 and 2026. Data collection techniques involved reading, noting, and categorizing information relevant to the research topic. Data analysis employed content analysis. The findings indicate that the Discovery Learning model effectively enhances elementary school students’ writing skills because students are more actively engaged in seeking information, developing ideas, structuring paragraphs, and presenting concepts systematically. Furthermore, the Discovery Learning model can also enhance students’ learning motivation, creativity, critical thinking skills, and participation in Indonesian language learning. Thus, the Discovery Learning model can serve as an alternative instructional model to improve elementary school students’ writing skills. Keywords: Discovery Learning, writing skills, elementary school students